2017
DOI: 10.1007/s11205-017-1646-9
|View full text |Cite
|
Sign up to set email alerts
|

Donating Time or Money? The Effects of Religiosity and Social Capital on Civic Engagement in Qatar

Abstract: Few studies have examined the role of religiosity and social capital on civic engagement in the context of a Muslim country. In this paper, we explore the impact of religiosity and social capital on charitable donations and volunteerism in Qatar. Drawing on a nationally representative survey from Qatar, we consider various attitudinal and behavioral measures for capturing religiosity and social capital. The results indicate that, even after controlling for a wide range of demographic variables, behavioral meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…We admit that religiosity measures such as identity, values, norms, and service attendance alongside private ritual practices are highly correlated and difficult to separate. Yet, our studies note enough distinctions between these categories to require a third independent mechanism, as these studies found contradictory results in how prayer-as the most commonly measured private religious ritual-affects giving to the outgroup (Diop et al 2018;Greenway et al 2018;Thunstrom 2020). Thunstrom (2020) shows there are actually two mechanisms in how prayer affects giving using experimental design.…”
Section: Private Ritualsmentioning
confidence: 59%
See 4 more Smart Citations
“…We admit that religiosity measures such as identity, values, norms, and service attendance alongside private ritual practices are highly correlated and difficult to separate. Yet, our studies note enough distinctions between these categories to require a third independent mechanism, as these studies found contradictory results in how prayer-as the most commonly measured private religious ritual-affects giving to the outgroup (Diop et al 2018;Greenway et al 2018;Thunstrom 2020). Thunstrom (2020) shows there are actually two mechanisms in how prayer affects giving using experimental design.…”
Section: Private Ritualsmentioning
confidence: 59%
“…To measure this form of religiosity, the studies used scales such as the family environment scale (FES), the supernatural belief scale, and other self-reported Likert-scales that range from 1 (not religious) to 10 (very religious). Studies also incorporated various dimensions of religiosity such as practice, belief, and experience, as well as the consequence or importance of religion in the participants' lives (Dilmaghani 2018;Diop et al 2018). A few studies also measured religiosity by asking if individuals followed specific religious practices such as keeping Shabbat or Kosher (Sansani and Rozental 2018).…”
Section: Religion and Giving To Out-outgroup And Secular Organizations Measuresmentioning
confidence: 99%
See 3 more Smart Citations